Sustitución del colorante sintético rojo No.40 por colorantes a base de antocianinas usando ciruela roja (2024)
The project proposes the change and replacement of red 40 dye, a synthetic food additive, with anthocyanins, natural compounds present in various foods such as fruits, vegetables and flowers that give red, violet and blue colors. Anthocyanins are considered safe and healthy, and their use could reduce exposure to artificial and potentially harmful substances. Thus Arrulla Red Dye (red dye 40), being one of the most harmful additives in the food industry due to its side effects and its composition requires a solution, thus the plum is proposed as the alternative in the project for the extraction of the pigment and the replacement of this supplement. The project proposes a methodology for the extraction of plum pigments, a study of the yield and extracted quantity of anthocyanins as an organoleptic test to evaluate the effectiveness of the organic component as a substitute. Thus, the thesis provides data for the feasibility in the industry and its possibility for changing products harmful to human consumption for more organic products.